Question

find the general solution by undetermined coefficients method. y′′-3y′+2y=-9x^2+6x

Answer #1

Use the method of Undetermined Coefficients to find the general
solution
y'' - y' -2y = e^(2x)

Find the general solution of y'' − 2y' = sin(5x) using the
method of undetermined coefficients

4. Find the general
solution to the homogeneous equation, then use the method of
undetermined coefficients to find the particular solution
y’’− 2y’ + 2y =
360e−t sin3t.

Use the method of undetermined coefficients to find a general
solution to the given differential equation:
y''-y'-2y=4te3t+4sin2t

use the method of undetermined coefficients to solve the
differential equation)
y'' + 2y' - 3y = (x2 + x + 1) + e-3x

use the method of undetermined coefficients to find
one solution of y"-2y'-y=8e^(4t)

Use the undetermined coefficients method to find the particular
solution of the differential equation y'' + 3y' - 4y =
xe2x and then write the general solution.

Use undetermined coefficients to find the particular solution
to
1) y''−2y'+3y= 5t^2+2t+2
yp(t)=?
2) y''+y'−20y= −2550sin(3t)
yp(t)=?

Solve the following second order differential equations:
(a) Find the general solution of y'' − 2y' = sin(3x) using the
method of undetermined coefficients.
(b) Find the general solution of y'' − 2y'− 3y = te^−t using the
method of variation of parameters.

X'= 6x-5y+e^5t
Y'= x+4y
Find the general solution using undetermined coefficients

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 1 minute ago

asked 8 minutes ago

asked 22 minutes ago

asked 36 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 2 hours ago

asked 2 hours ago

asked 2 hours ago